Design and Analysis of a Step-Up Multi-Port Converter Applicable for Energy Conversion in Photovoltaic Battery Systems - Siyuan Shi; Song Xu; Wei Jiang; Seiji Hashimoto (Energies, 2023)
Aiming at the problems of large power fluctuations and poor stability in photovoltaic and other new energy power generation systems, a step-up multiport converter (MPC) that can simultaneously connect low-voltage photovoltaic cells, batteries, and loads (independent loads or power grids) is proposed in this manuscript. According to the possible operating conditions of the system, the working principles are described in detail. Theoretical analysis based on different working modes is presented and a hybrid modulation control method including pulse width modulation (PWM) and phase shift modulation (PSM) are applied to realize energy transmission between photovoltaics, batteries, and power grids. A simulation model is built in the PSIM environment to validate each working state of the system and mode switching function. Experiments are carried out on an experimental platform using the dsPIC33FJ64GS606 digital microcontroller as the control center, and the experimental results successfully verify the system function and PWM + PSM control efficiency.